The Effect Of Honey Administration On Hemoglobin Levels Of Pregnant Women Trimester II - Br Sianturi, Marta Imelda; Sinaga, Elvipson; Batubara, Khairunnisa (Jurnal EduHealth, 2022)
During pregnancy, there are many problems experienced by pregnant women, one of which is anemia in pregnancy which is characterized by low Hb levels. Anemia in pregnant women can cause increased problems in pregnancy and childbirth. Pregnant women who have anemia will be very at risk of the birth of premature babies. Based on the results of a survey at the Chainny Rhamawan clinic, there were 20 anemic second trimester pregnant women. The purpose of this study was to determine the effect of honey administration on increasing Hb levels of pregnant women in the second trimester. Research method using experimental research method with group pretest-posttest design-. The sampling technique is Purposive so that a sample of 10 people is obtained. The instruments used are from documentation and inform concent sheets. The analysis was performed with paired t-tests. The results of the study obtained the effect of honey administration on the Hb levels of mothers in the second trimester with a p-value of 0.002 and this - value of <0.05. So giving honey to mothers regularly can increase the Hb levels of pregnant women, therefore midwives can provide information to pregnant women about the benefits of honey in pregnancy.